Engaged Versus Disengaged: The Role Of Occupational Self-Efficacy - Chaudhary, Richa; Rangnekar, Santosh; Barua, Mukesh Kumar (Asian Academy of Management (AAM), 2013)
The fundamental aim of the present study of 126 business executives was to examine whether an engaged workforce could be differentiated from its disengaged counterpart based on occupational self-efficacy, which is an individual difference variable. We anticipated that work engagement would be characterised by high occupational selfefficacy and therefore predicted that it would positively correlate with occupational selfefficacy. Fisher's linear discriminant analysis was used to distinguish engaged employees from disengaged ones. The results showed that the command and adaptability dimensions of self-efficacy are found to be the most important in distinguishing engaged employees from their non-engaged counterparts. A logistic regression analysis was also carried out to determine whether socio-demographic variables contributed to group differences. The results of the logistic regression supported the findings of the discriminant analysis.